2022
DOI: 10.1017/s000305542200051x
|View full text |Cite
|
Sign up to set email alerts
|

White Americans’ Reactions to Racial Disparities in COVID-19

Abstract: I fielded a survey experiment on a nationally representative sample of 591 white Americans to test whether exposure to information about the disparate impact of COVID-19 on Black people influenced white Americans’ opinion about COVID-19 policies. I found that racially prejudiced white Americans who were exposed to the treatment diminished the importance of wearing a face mask. They also became more supportive of outdoor activities without social distancing guidelines, more likely to perceive shelter-in-place o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…29,30 News framing of health risks as particularly pertaining to ethnic and racial minority groups has also been shown to decrease support for preventive behaviors among White Americans 31 and for public health policies. 32 As such, well-intentioned efforts to use communication to achieve health equity need to reconsider how—indeed, whether —to present health disparities.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 News framing of health risks as particularly pertaining to ethnic and racial minority groups has also been shown to decrease support for preventive behaviors among White Americans 31 and for public health policies. 32 As such, well-intentioned efforts to use communication to achieve health equity need to reconsider how—indeed, whether —to present health disparities.…”
Section: Resultsmentioning
confidence: 99%
“…These racist responses have been documented across a variety of health and social policy domains, though they appeared most frequently in the context of crime, incarceration, poverty, and unemployment. Although not within the timeframe of this scoping review (which was limited to studies published until April 2021), recent evidence shows that these patterns of racist responses to racial comparisons have persisted in the context of devastating racial inequities in deaths from COVID‐19 106,107 . Several studies suggest that these patterns may be driven by the fact that White respondents default to behavioral (for crime, incarceration, poverty, and unemployment) and/or biological or behavioral (for health) causal attributions for these outcomes and disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have already established that, among prejudiced Whites, exposure to racial disparities reduced concern about the pandemic and support for mitigation policies (Harell & Lieberman, 2021; Stephens‐Dougan, 2022). More worryingly, another study found that white participants who were primed with exposure to the persistence of inequalities underlying racial disparities (vs. not exposed) expressed less concern about COVID‐19 (Skinner‐Dorkenoo et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have already established that, among prejudiced Whites, exposure to racial disparities reduced concern about the pandemic and support for mitigation policies (Harell & Lieberman, 2021;Stephens-Dougan, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation